Engaging a School’s Leadership Team in Re-envisioning Professional Learning for Public Secondary Educators through the PAR Experience in Cambodia - Sarom Mok; Ramy Chhun; Sophay Sim; Satya Yen; Sophal Yoeun (Journal of Law and Social Politics, 2026)
Background: Professional development (PD) for public secondary educators is commonly one-size-fits-all, fragmented, and short-term, lacking a coherent vision for collaborative teaching and learning. Such opportunities rarely model the creativity and depth required in classrooms, leading teachers to doubt district-mandated sessions and limit participation to compulsory trainings. Despite growing interest in Participatory Action Research (PAR), little evidence exists on how it can reshape professional learning within Cambodian secondary schools. Objective: This study examined the experiences of a school’s leadership team as participants in PAR to identify the resources educators need to acquire the skills and knowledge that make a difference for students. Methods: Grounded in teamwork, the PAR positioned participants as co-researchers who assessed resource needs, reviewed existing procedures, and devised workable plans; the study was conducted with participants rather than on them to bridge research and practice. Results: Findings revealed the need for a more diversified, transparent, and strategic PD framework, including expanded online and hybrid options, clearer training requirements, differentiation by experience, subject, and role, stronger peer collaboration and learning committees, and attention to structural barriers such as workload, coverage, and funding. Conclusion: A collaborative PAR approach empowers educators to own their PD, producing relevant, context-responsive systems that enhance teacher practice and student achievement.